Pengaruh Kombinasi Enzim Pektinesterase dan Poligalakturonase terhadap Klarifikasi Sari Buah Apel Varietas Manalagi - Esti Widowati; Rohula Utami; Bambang Sigit Amanto; Edwi Mahadjoeno; Agrizka Armunanta Putri (agriTECH, 2020)
Apple is a fruit with numerous nutrient content alongised high levels of harvest and consumption. The Manalagi is one of the varieties grown in Indonesia,characterized by a yellowish green coloration, sweet taste, as well as easy rot and damage potentials. Hence, many people have encouraged the need to process raw samples into processed juice products. This practice raises the sale value and prolongs the shelflife. However, the apple juice have a major challenge of easy browning and turbidity, resulting from the pectin content. Furthermore, removal is harder due to turbity, exceptthrough enzymatic depectination, with the pectinase enzymes, particularly pectinesterase (PE) and polygalacturonase (PG). The presence of these materials in the juice mixture leads to inherent pectin degradation into smaller fractions and consequently ensures clarity. In addition, the research involved Completely Randomized Factorial Design (CRFD) with two factors, including enzyme concentration (0.5% and 1%) and PG:PE ratio (1: 5, 1: 2, 1: 1, 2: 1; 5 : 1). Therefore, the data obtained were analyzed using two way ANOVA with 5% significance level. The variance analysis result showed the effect of concentration on pH and transmittance value, while the ratio influences Total Soluble Solid (TSS) and transmittance value. In addition, both variables collectively affect pH and viscosity values. The best treatment for manalagi apple juice clarification was obtained with 0.5% concentration samples and PG: PE ratio 5:1.